Developing peer mentors’ collaborative and metacognitive skills with a technology-enhanced peer learning program - CARVALHO, Ana Raquel; SANTOS, Carlos (Computers and education open, 2022)
•21st century skills’ development benefits from active learning pedagogies.•The impact of participation in a technology-enhanced peer learning program is assessed.•The peer learning program had a positive impact on peer mentors’ metacognitive awareness.•The peer learning program had a positive impact on peer mentors’ collaborative skills.•Digital technologies had a critical role in supporting peer mentors’ participation. Learning in the 21st century is influenced by a new paradigm regarding the human relationship with knowledge. The change from knowledge transmission to knowledge construction assumes a central role for the development of 21st century key competencies. Despite this, more evidence is required regarding the impact of active learning approaches on the development of such skills, especially metacognitive and collaborative skills. The present study reports findings on the impact of a technology-enhanced peer learning program on the promotion of upper secondary English as a Foreign Language student mentors’ metacognitive and collaborative skills as well as on how digital technologies (social media, multimedia production and collaborative online tools) contributed to their participation. 47 mentors from three Portuguese K-12 schools integrated the sample. Developed within the scope of Educational Design Research, the study follows a mixed-methods approach and combines quantitative and qualitative data from two self-report measurement tools and a survey by questionnaire. Data were analyzed by means of descriptive and inferential statistics and content analysis. Study findings confirmed that participation in the peer learning program had a positive impact on mentors’ metacognitive awareness and on the development of communication and collaboration skills related competencies - interaction and sharing with technologies, adding new evidence of the effectiveness of an innovative peer learning program design as to the deployment of 21st skills on secondary education. Study findings also indicated that the role of digital technologies was critical to supporting mentors’ collaborative work and interaction with their peers while participating in the program.